2017
DOI: 10.4018/978-1-5225-2446-5.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Using OpenStreetMap to Create Land Use and Land Cover Maps

Abstract: OpenStreetMap (OSM) is a bottom up community-driven initiative to create a global map of the world. Yet the application of OSM to land use and land cover (LULC) mapping is still largely unexploited due to problems with inconsistencies in the data and harmonization of LULC nomenclatures with OSM. This chapter outlines an automated methodology for creating LULC maps using the nomenclature of two European LULC products: the Urban Atlas (UA) and CORINE Land Cover (CLC). The method is applied to two regions in Lond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Arsanjani et al [3] tested the conversion of OSM data into a LULC map using the Urban Atlas nomenclature with encouraging results. Fonte et al [8,10] proposed an automated methodology to convert OSM data into LULC maps and Fonte et al [9] showed the potential of merging LULC data extracted from OSM with existing LULC products, namely the GlobeLand30. The use of OSM extracted LULC data to validate LULC maps was also tested with promising results, as for Urban Atlas level 1 nomenclature the accuracy indices obtained using OSM data (where available) to obtain the reference class were not very different from the ones obtained when the reference class was always obtained by photo interpretation [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arsanjani et al [3] tested the conversion of OSM data into a LULC map using the Urban Atlas nomenclature with encouraging results. Fonte et al [8,10] proposed an automated methodology to convert OSM data into LULC maps and Fonte et al [9] showed the potential of merging LULC data extracted from OSM with existing LULC products, namely the GlobeLand30. The use of OSM extracted LULC data to validate LULC maps was also tested with promising results, as for Urban Atlas level 1 nomenclature the accuracy indices obtained using OSM data (where available) to obtain the reference class were not very different from the ones obtained when the reference class was always obtained by photo interpretation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Shultz et al [29] produced a global Land Cover product using OSM data, and used the available data to train a classifier that was used to classify satellite imagery in order to generate data for the regions when OSM data is not available. The encouraging results obtained in the previous efforts motivated the creation of OSM2LULCa FOSS4G aiming to automatically convert OSM data into LULC maps [8][9][10]. OSM2LULC 2 is part of the GeoData Algorithms for Spatial Problems (GASP) Python package, 3 whose ultimate aim is to provide various tools to extract, to convert, to analyse, and to validate geospatial information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the coverage and the quality of the annotations from open GIS vary a lot depending on the users' knowledge and number of contributors, this data may contain relevant information for mapping specific areas and classes. A deterministic framework to create land use and land cover maps from crowdsourced maps such as OSM data was proposed in [10]. Machine learning tools (a random forest variant) also allow coupling remote sensing and volunteered geographic information (VGI) to predict natural hazard exposure [11] and local climate zones [8], while active deep learning helps finding unlabeled objects in OSM [5].…”
Section: Related Workmentioning
confidence: 99%
“…This inspired further investigation to employ CGI for changes detection to complement the shortcoming of remote sensing. A recent research study proposed a method of generating up-to-date maps using textual information from OSM [17,18]. Since these kinds of data were provided by volunteers, textual information is often insufficient and incomplete for rapid LCC detection.…”
Section: Introductionmentioning
confidence: 99%